1990
DOI: 10.1523/jneurosci.10-07-02039.1990
|View full text |Cite
|
Sign up to set email alerts
|

Making arm movements within different parts of space: dynamic aspects in the primate motor cortex

Abstract: The activity of 176 individual cells in the arm area of motor cortex (areas 4 and 6) was studied while monkeys made arm movements of similar direction within different parts of extrapersonal space. The behavioral paradigm used was a 3-dimensional reaction-time task aimed at dissociating the direction of movement, which remained similar across the work space, from the patterns of muscular activity and the angular joint excursions necessary to perform these movements. In agreement with other studies (Georgopoulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
266
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(299 citation statements)
references
References 44 publications
31
266
2
Order By: Relevance
“…The activity of cell populations is greatest for hand movements in a particular direction and decreases progressivelyas direction changes. Similar patterns have been reported in motor cortex (Caminiti et al 1990;Georgopoulos et al 1982Georgopoulos et al . 1986Kalaska et al 1989;Schwartz et al 1988), cerebellarcortex (Fortieret al 1989).…”
Section: Frame Of Reference For Motion Planningsupporting
confidence: 89%
“…The activity of cell populations is greatest for hand movements in a particular direction and decreases progressivelyas direction changes. Similar patterns have been reported in motor cortex (Caminiti et al 1990;Georgopoulos et al 1982Georgopoulos et al . 1986Kalaska et al 1989;Schwartz et al 1988), cerebellarcortex (Fortieret al 1989).…”
Section: Frame Of Reference For Motion Planningsupporting
confidence: 89%
“…The multiplicative relationship between the GO signal and a desired movement vector as exemplified by Equation 9 has been used to explain a very large amount of data from the movement control literature (Bullock & Grossberg, 1988), including data on synchronous movement completion by different joints (Freund & Budingen, 1978), muscle contraction duration in variance (Freund & Budingen, 1978;Ghez & Vicario, 1978), bell-shaped velocity profiles (Howarth & Beggs, 1971), changing velocity profile asymmetry at higher movement speeds (Beggs & Howarth, 1972;Zelaznik, Schmidt, & Gielen, 1986), amplification of peak velocity during target switching (Georgopoulos, Kalaska, & Massey, 1981), and speed-accuracy trade-offs (Fitts, 1954;Woodworth, 1899). Furthermore, Guenther (1992) and Bullock et al (1993) showed that directional tuning curve properties of neurons used in such a mechanism closely match the properties of cells found in monkey motor cortex (e.g., Caminiti, Johnson, & Urbano, 1990;Georgopoulos, Kalaska, Caminiti, & Massey, 1982).…”
Section: Speaking Rate Effectsmentioning
confidence: 88%
“…Furthermore, Guenther (1992) and Bullock eta!. (1993) showed that directional tuning curve properties of neurons utilized in such a mechanism closely match the properties of cells found in monkey motor cortex (e.g., Georgopoulos, Kalaska, Caminiti, and Massey, 1982;Caminiti, Johnson, and Urbano, 1990). …”
Section: Speaking Rate Effectsmentioning
confidence: 88%
“…Arm posture , wrist rotation (Kakei et al, 1999), and changes in the starting location (Caminiti et al, 1990) modulate directional selectivity in M1, suggesting that this area contains neuronal populations that represent movement direction at the level of parameters such as muscle forces and joint angles (Todorov, 2003).…”
Section: Introductionmentioning
confidence: 99%